A Centrifuge Modelling and Finite Element Analysis of Laterally Loaded Single Piles in Sand with Focus on P–Y Curves - Haouari, Hocine; Bouafia, Ali (Periodica Polytechnica Civil Engineering, 2020)
Centrifuge modelling and finite element analysis are powerful tools of research on the lateral pile/soil interaction. This paper aims at presenting the main results of experimental and numerical analysis of the pile response under monotonic lateral loading in sand. After description of the experimental devices, it focuses on the determination of the load-transfer P-Y curves for rigid and semi-rigid piles embedded in dry dense sand by using the experimental bending moment profiles obtained in centrifuge tests, as well as by a three-dimensional finite element models using ABAQUS Software. The elastic perfectly plastic Mohr-Coulomb constitutive model has been used to describe the soil response, and the surface-to-surface contact method of ABAQUS software has been used to take into account the nonlinear response at soil/pile interface. The analysis methodology has allowed to propose a hyperbolic function as a model to construct P-Y curves for rigid and semi-rigid piles embedded in dry dense sand, this model is governed by two main parameters, which are the initial subgrade reaction modulus, and the lateral soil resistance, the latter has been formulated in terms of Rankine’s passive earth pressure coefficient, the sand dry unit weight, and the pile diameter.